2023
DOI: 10.1002/oby.23784
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for obesity in adulthood among survivors of childhood cancer

Laurène Delacourt,
Rodrigue Allodji,
Juliette Chappat
et al.

Abstract: Objective The aim of this study was to identify risk factors for obesity in childhood cancer survivors (CCSs). Methods The study included 3199 patients of the French Childhood Cancer Survivor Study cohort, with 303 patients with obesity who had returned the self‐questionnaire. Analyses were adjusted for social deprivation index and sex. Results CCSs were less likely to have obesity (9.5%; 95% CI: 8.5%–10.5%) than expected from the general French population rates (12.5%; p = 0.0001). Nevertheless, brain tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Chow et al found that CVD risk factors are underdiagnosed in >25% of adult CCS and undertreated ~20% of the time, with the greatest risk associated with elevated BMI and/or adverse lifestyle factors (12). Although certain therapeutic exposures can predispose survivors to high BMI, overweight/obesity rates among CCS are similar to those of the general population (16)(17)(18)(19). Large national and international population-based cohort studies have contributed tremendously to our understanding of late effects associated with individual therapies (20)(21)(22)(23).…”
Section: Modifiable Lifestyle Factors and Chronic Health Conditions A...mentioning
confidence: 99%
“…Chow et al found that CVD risk factors are underdiagnosed in >25% of adult CCS and undertreated ~20% of the time, with the greatest risk associated with elevated BMI and/or adverse lifestyle factors (12). Although certain therapeutic exposures can predispose survivors to high BMI, overweight/obesity rates among CCS are similar to those of the general population (16)(17)(18)(19). Large national and international population-based cohort studies have contributed tremendously to our understanding of late effects associated with individual therapies (20)(21)(22)(23).…”
Section: Modifiable Lifestyle Factors and Chronic Health Conditions A...mentioning
confidence: 99%